BUDIDAYA TERPADU LELE DUMBO DENGAN TANAMAN ECENG GONDOK (Eichornia crassipes), KANGKUNG AIR (Ipomea aquatica) DAN KAPU-KAPU (Pistia stratiotes) - Bambang Triyatmo; Namastra Probosunu (Universitas Gadjah Mada, 2002)
Catfish (Clarias gariepinus) was cultured with an aquatic plant, water hyacinth/eceng gondok (Eichornia crassipes), kangkung air (Ipomea aquatica) or kapu-kapu (Pistia stratiotes) in concrete ponds, for 3 months. Catfish cultured without aquatic plant was used as a control. The experiment was carried out to evaluate the survival rate as well as the growth of fish and aquatic plants.The survival rates of catfish cultured with I. aquatica, E. crassipes, and P. stratiotes were 76, 87, and 98%, respectively. In addition the survival rate of catfish cultured without any aquatic plant was 93%. The weight gain of catfish was 14,1-16,2 kg per pond. Whereas, the total weight gains of aquatic plant were 37,0, 27,7 and 7,7 kg per pond for E. crassipes, P. stratiotes, and I. aquatica,. Respectively. Dissolved oxygen, and the concentrations of NH3, NH4+ and PO43- in water with aquatic plants were higher than that of in water without aquatic plant. However, the concentration of CO2 was higher in water with aquatic plant.